Temporal variation and interaction of full size spectrum Alcian blue stainable materials and water quality parameters in a reservoir. (July 2015) - Thuy, Nguyen Thi; Lin, Justin Chun-Te; Juang, Yaju; Huang, Chihpin
Graphical abstract: Highlights: We study Alcian blue (AB) stained fractions in freshwater for one year, intensively during phytoplankton bloom. Sampling frequency and species composition are important for linking AB stained material and phytoplankton. AB stained particles and pTEP are generated directly from some phytoplankton species instead of by abiotic pathway. FlowCAM is a promising technique for AB stained particles visualization. Abstract: This paper reports on the fate of different fractions of Alcian blue (AB) stainable material in Pao-Shan reservoir, Taiwan, in a one-year study (2013–2014) and an intensive study during phytoplankton bloom (2014). The interactions between the fractions, including AB stained particles, particle and colloidal transparent exopolymer particles (pTEP and cTEP), dissolved acid polysaccharide (dAPS), and their relationship to other water quality parameters were analyzed. The Flow Cytometer and Microscope (FlowCAM) was for first time used to characterize AB stained particles. The results of the one-year study likely showed relationships of pTEP concentration to phytoplankton count and chlorophyll a, while in the intensive study, AB stained particles abundance and pTEP concentration were correlated neither phytoplankton count nor chlorophyll a, but strongly positively correlated with some phytoplankton species' abundance. The difference indicates that sampling frequency and phytoplankton composition should be addressed for studying the links between AB stained fractions and phytoplankton. The interaction between different AB stained fractions further suggests that the majority of AB stained particles and pTEP would be directly generated by some phytoplankton species, whereas their abiotic generation by cTEP or dAPS may only have contributed partly to their formation. This differs from previous studies which generally posited that pTEP are mainly formed abiotically from dissolved precursors. Successful application of FlowCAM for visualization of AB stained particles recommends this technique by which particle morphologies can be conserved and morphological features of particle can be simultaneously elucidated.